METACOMMENTARY IN ENGLISH VINGLISH MOVIE - Isti’anatul Hikmah; Mohammad Saddam Hussein (JELLT (Journal of English Language and Language Teaching), 2019)
This study analysed David Fischer’s utterances in English Vinglish movie using metacommentary. His utterances will be classified based on six types of metacommentary namely metacommentary type 1, 2, 3, 4, 5, and 6. The aims of this study were describing types of metacommentary used by David Fischer and explaining reasons behind it. This study used qualitative method which was divided into three those were method of collecting data using simak method; method of analysing data using descriptive analytic method; and method of presenting data analysis using informal method. Findings of this study showed that all six metacommentary types were found in David Fischer’s utterances. Metacommentary type one-marking code was used when his students started to use their native language, so it was a control for them to continue using English. Metacommentary type two-marking the sounds of language was used when his students pronounce English using their native language pronunciation, and it appeared in compliment because it aimed to appreciate and improve students’ self-confidence using English. Metacommentary type three-marking address term was used when his students have sufficient English skills, and it aimed to minimize negative effects of his utterances which he gave comments to his students. Metacommentary type four-gesture was used to clarify his utterances and to reduce bad effect of his utterances to his students. Metacommentary type five- comments on clothing, appearance was used to improve his students’ confidence. Metacommentary type six-irony contained implied meaning, and it was used to cover students’ weakness in English therefore students will not be hurt.